Leptospira dzianensis and Leptospira putramalaysiae are later heterotypic synonyms of Leptospira yasudae and Leptospira stimsonii. Issue 3 (23rd March 2021) - Casanovas-Massana, Arnau; Vincent, Antony T.; Bourhy, Pascale; Neela, Vasantha Kumari; Veyrier, Frederic J.; Picardeau, Mathieu; Wunder Jr., Elsio A.
Abstract : Leptospira dzianensis and Leptospira putramalaysiae were recently described as novel species and published almost concurrently with Leptospira yasudae and Leptospira stimsonii . Genome comparisons based on average nucleotide identity of the type strain genomes indicate that L. dzianensis and L. putramalaysiae are conspecific with L. yasudae and L. stimsonii, respectively. Based on the rules of priority, L. dzianensis should be reclassified as a later heterotypic synonym of L. yasudae, and L. putramalaysiae should be reclassified as a later heterotypic synonym of L. stimsonii .